Literasi Keuangan dalam Meningkatkan Minat Investasi pada Generasi Milenial di Pulau Bawean - Dhita Febyanti; Anita Akhirruddin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of financial literacy, financial inclusion and lifestyle on the investment interest of the millennial generation on Bawean Island. The millennial generation in this region, numbering 18,095 people, has great potential to increase economic growth through investment. However, the level of financial literacy and understanding regarding financial inclusion among them is still low. The research used a quantitative method with a survey approach, involving 100 respondents selected using a simple random sampling technique. Data collection was carried out through questionnaires, and data analysis used multiple linear regression. The research results show that financial literacy, financial inclusion and lifestyle significantly influence investment interest. Financial literacy provides a deep understanding of risk management and investment decision making, while financial inclusion increases access to financial services. Lifestyle also plays an important role in encouraging more productive investment behavior. This research contributes to efforts to develop policies that support increasing financial literacy and inclusion to encourage wider investment participation among the millennial generation, especially in the Bawean Island area.